Além das telas: práticas de lazer de turistas motivados pelo audiovisual - João Lucas de Almeida Campos (2022)
By portraying different landscapes and cultures, audiovisual productions can arouse the interest of spectators in knowing the locations shown on the screen. Based on this premise, this dissertation aimed to understand how tourists motivated by audiovisual productions experience tourism as a leisure experience. Regarding the specific objectives, this work proposed to identify the motivations, characteristics of the trips and, also, to identify and discuss the leisure practices experienced in the destination visited by these tourists. The theoretical-conceptual foundations of this research include its key themes, in order to understand the connections between leisure and tourism, the main theories about tourism motivated by audiovisual in terms of conceptions, practices and types. It was also sought to deepen knowledge about the "film tourist", the subject studied here. The methodology of this qualitative investigation of the descriptive type used, as an instrument of data collection, an online questionnaire with closed and open questions, applied by the google forms platform. In all, 117 volunteers participated, recruited through the dissemination of the research on social networks, and invitations sent by e-mail. To analyze the qualitative data, the content analysis proposed by Laville and Dionne (1999) was chosen, with the help of word clouds generated by the Nvivo software. The results show that international audiovisual productions were the main inducers, with films being the most consumed product. In this way, international destinations were mostly chosen by the group, to enjoy audiovisual-induced tourism. In addition, tourists performed various leisure activities related to audiovisual, highlighting the visit to places shown on the screen: parks, squares and cultural heritage. They also experienced the gastronomy of foods and drinks depicted on screens. In general, the trip met the expectations of these tourists and aroused feelings of enchantment, self-fulfillment and nostalgia. The perception about the destinations visited is that what was portrayed on the screen matches what was found at the place of visit. It is concluded that the expectations of the surveyed film tourists were met, as they claimed to be satisfied with their experience. However, as much as tourism motivated by audiovisual productions is a reality in some tourist destinations, it is not so simple to achieve in any location, as literature often romanticizes.